- #1

- 1

- 0

g(x)= ( 1+4x )

^{5}( 3+x-x

^{2})

^{8}

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter Heinz21
- Start date

- #1

- 1

- 0

g(x)= ( 1+4x )

- #2

mathman

Science Advisor

- 8,008

- 518

The g(x)=f(x)h(x) and g'(x)=f(x)h'(x) + f'(x)h(x)

Can you do the rest yourself?

- #3

- 192

- 3

Then each derivative [h ' (x) and f ' (x) ] will require using The Chain Rule.

Share: